Physical, Phytochemical Screening And Antibacterial Activities Of Clerodendron Infortunatum Linn Root - Dr. N.A. ALEY KUTTY,; SANTHOSH M. MATHEWS,; LEENA P.N., (International Journal of Pharma and Bio Sciences, 2011)
Plant materials are used throughout developed and developing countries as home remedies, over the counter drug products and raw materials for the pharmaceutical industry and represent a substantial proportion of the global drug market. It is therefore essential to establish internationally recognized guidelines for assessing their quality. Some of quality control parameters of the roots of Clerodendron infortunatam belonging to Verbenceae family were analyzed. It includes root powder characters, moisture content determination by LOD method, FOM determination, Rf value detection by TLC, using different solvents, Ashvalues, extractive values. The root portions of Clerodendron infortunatum Linn extracted with ethanol, chloroform by cold maceration process .The extracts were vaccum dried and subjected to antibacterial (Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Klebsiella pneumoniae) screening by Agar disc diffusion method. Minimum Inhibitory Concentration of microbial growth was also evaluated. The phytochemical screening was performed and different phytoconstituents present in the extracts were identified .The extracts exhibited potent activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Klebsiella pneumoniae.